Don Knotts : 4 movie collection [videorecording (DVD)] - Knotts, Don, 1924-2006; Conway, Tim; Bixby, Bill, 1934-1993; Clark, Susan, 1940-; Wayne, David, 1914-1995; Pickens, Slim; Asner, Edward; Elam, Jack, 1920-2003; Valentine, Karen, 1947-; McGavin, Darren, 1922-2006; Anderson, Bill, 1911-1997; Tait, Don; et al. (Walt Disney Pictures, 2012)
Apple Dumpling Gang: Three orphan children strike gold in 1878 California.